2017
DOI: 10.1002/celc.201700058
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active PdCu Alloy Nanowire Network Electrocatalyst for Ethanol and Methanol Electrooxidation

Abstract: PdCu alloy nanowire networks (NNWs) with tunable compositions are synthesized. Electrooxidaton catalytic measurements prove that the as‐prepared PdCu NNWs represent a predominant catalyst for methanol and ethanol electrooxidation reactions in alkaline medium. With increasing copper content, the electrocatalytic activity of the catalytic materials to ethanol and methanol was significantly increased. Pd27Cu73 NNW‐modified electrodes display superior catalytic activity (8300 A gPd−1) toward the ethanol electrooxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…As illustrated in Figure c, the peaks situated at 335.5 eV and 340.8 eV are attributed to metallic state of Pd. And the peaks located at 336.9 eV and 342.0 eV can be ascribed to Pd II . It is readily found that metallic state is the dominated chemical valence state of Pd in PdCu NCs by comparing the intensity of these peaks.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…As illustrated in Figure c, the peaks situated at 335.5 eV and 340.8 eV are attributed to metallic state of Pd. And the peaks located at 336.9 eV and 342.0 eV can be ascribed to Pd II . It is readily found that metallic state is the dominated chemical valence state of Pd in PdCu NCs by comparing the intensity of these peaks.…”
Section: Resultsmentioning
confidence: 94%
“…And the peaks located at 336.9 eV and 342.0 eV can be ascribed to Pd II . [48,49] It is readily found that metallic state is the dominated chemical valence state of Pd in PdCu NCs by comparing the intensity of these peaks. Similarly,a si llustrated in Figure 3d,t he peaks situated at 932.0 and 954.1 eV are assigned to metallic state of Cu and the weaker peaks situated at 934.4 and 954.1 eV suggest the existence of Cu II .T he satellite peaks situated at 942.3 and 963.2 eV are corresponded to CuO whicha re caused by oxidation of Cu on the surface of PdCu NCs.…”
Section: Resultsmentioning
confidence: 99%
“…The one dimensional network is characterized by its high electron transport rate as a result of the path‐directing effect of the structure anisotropy [169,226,227] as well as the large surface area provided by the protein support [70] . The polyhedrin was also reported to be a versatile template for the synthesis of PdCu alloy nanowire networks and further applied to methanol and ethanol electrooxidation [168] . By tuning the Pd/Cu ratio, it was found that with increasing Cu content, the catalytic activity also increased, which was attributed to the Cu modifying the d‐band structure of Pd and thus changing the interatomic charge transfer between the two components.…”
Section: Applications Of Bio‐templated Mnms For Different Electrocatamentioning
confidence: 99%
“…Thus, it is essential to reduce the quantity of Pt utilised in fuel cells. It has already been reported that palladium‐based nanostructured materials offered moderate catalytic activity for various electrochemical reactions in fuel cells . There are few reports on the usage of Pd NPs for direct methanol and ethanol fuel cells (DMFCs and DEFCs) …”
Section: Introductionmentioning
confidence: 99%